Theoretical Study of the Nernst Effect in Compositional Superlattices in the Presence of Strong Electromagnetic Wave - Ba, Cao Thi Vi; Huong, Nguyen Thu; Duy, Tran Khuong; Nhan, Nguyen Thi Thanh (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1DO - 10.25073/2588-1124/vnumap.4864, 2024)
The Nernst effect has been theoretically studied in compositional superlattice in the presence of a strong electromagnetic wave. Using the quantum kinetic equation for electrons with two cases electrons-acoustic phonons scattering and electrons-optical phonons scattering, we obtained the analytic expression of the Nernst coefficient and kinetic tensors as a function of the magnetic field, temperature, frequency, and amplitude of the electromagnetic wave and parameters of the compositional superlattice. The dependence of the Nernst coefficient on the magnetic field and temperature is achieved by numerical calculations for AlGa/AlGaAs material. The result indicates that in the case of electron-acoustic phonon scattering, the Shubnikov-de Hass oscillation appears. Whereas, in the case of electrons-optical phonons scattering, the peak of magneto-photon-phonon resonance appears. In both cases, when temperature increases, the Nernst coefficient decreases rapidly, and for electrons-optical phonons scattering, the resonance peak has a movement.